Testosterone and the Heart - Michael Kirby; Geoffrey Hackett; Sudarshan Ramachandran (European Cardiology Review)
The development of a subnormal level of testosterone (T) is not universal in ageing men, with 75% of men retaining normal levels. However, a substantial number of men do develop T deficiency (TD), with many of them carrying a portfolio of cardiovascular (CV) risk factors, including type 2 diabetes (T2D) and the metabolic syndrome. TD increases the risk of CV disease (CVD) and the risk of developing T2D and the metabolic syndrome. The key symptoms suggesting low T are sexual in nature, including erectile dysfunction (ED), loss of night-time erections and reduced libido. Many men with heart disease, if asked, admit to ED being present; a problem that is often compounded by drugs used to treat CVD. A large number of studies and meta-analyses have provided evidence of the link between TD and an increase in CVD and total mortality. Patients with chronic heart failure (CHF) who have TD have a poor prognosis and this is associated with more frequent admissions and increased mortality compared with those who do not have TD. Conversely, in men with symptoms and documented TD, T therapy has been shown to have beneficial effects, namely improvement in exercise capacity in patients with CHF, improvement of myocardial ischaemia and coronary artery disease. Reductions in BMI and waist circumference, and improvements in glycaemic control and lipid profiles, are observed in T-deficient men receiving T therapy. These effects might be expected to translate into benefits and there are more than 100 studies showing CV benefit or improved CV risk factors with T therapy. There are flawed retrospective and prescribing data studies that have suggested increased mortality in treated men, which has led to regulatory warnings, and one placebo-controlled study demonstrating an increase in coronary artery non-calcified and total plaque volumes in men treated with T, which is open for debate. Men with ED and TD who fail to respond to phosphodiesterase type 5 (PDE5) inhibitors can be salvaged by treating the TD. There are data to suggest that T and PDE5 inhibitors may act synergistically to reduce CV risk.